Perception of Actors who Participate in Inclusive Educational Programs in Higher Education - Morales Bacarrezza, Paz; Aguilera Cortés, María Consuelo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
It is relevant to interpret the perception that students with disabilities, teachers, and managers have about an inclusive educational program, to identify and describe the facilitators and barriers during the training of those students; analyze the relevance of the inclusive program from the perceptions of the participating actors; and assess the program's supports from the perception of students with disabilities. This is a mixed investigation of sequential design and phenomenological approach carried out through surveys and in-depth interviews with the actors.